Inspection of a duodenoscope working channel after a double positive sampling: case report and literature review. (1st February 2022) - Minciullo, Andrea; Colombo, Benedetta; Tartaglini, Daniela; Filomeno, Lucia; Maria Di Matteo, Francesco
Abstract : In contemporary endoscopy practice, it is possible and desirable to verify the integrity of the operating channel by inserting a video camera inside the endoscope. However, the right time to perform visual inspections remains uncertain. This article describes an inspection of the duodenoscope's working channel from the distal tip to the control section using the SpyGlass DS Direct Visualization System (Boston Scientific, Natick (MA), USA) and the SpyScope DS Catheter. The investigation made it possible to identify stains, debris and the wear of a gasket that could justify positive cultures, despite the correct adherence to the guidelines for the reconditioning of endoscopes. The routine inspection of the endoscope's channels could be a way to verify correct reprocessing in parallel with microbiological analyses and to identify endoscopes that need maintenance before the damage inside them can become more serious.